Apparitions 21 stories of ghosts, spirits, and mysterious manifestations--with exercises for developing reading comprehension and critical thinking skills - Billings, Henry (Critical reading series, 1999)
Nonfiction articles examining reports of haunted houses and ghostly appearances. Each is followed by reading comprehension and critical thinking exercises.